The Impact of Digital Media on the Religious Behavior of Youth: An Analytical Study in the Information Age (Journal of the College of Basic Education, 2026)
The study aimed to identify the extent of the impact of digital media on the religious behavior of young people. To achieve the research objective and solve its problem, a descriptive analytical approach was used. Data was collected and analyzed to describe the impact of digital media on the religious behavior of young people. The study concluded that the role of digital media in Iraq is high, from the perspective of the research sample. The arithmetic mean value reached 4.115 with a standard deviation of 0.770. The study also found a statistically significant effect of digital media on the religious practices of young people in Iraq at 0.05, and a strong direct correlation between the two variables. It showed that every time the level of digital media increased by 1%, the level of religious practices of young people in Iraq increased by 0.249%. Therefore, the study recommends the need to work on increasing the capacity of digital media to publicize the efforts being made to achieve religious awareness in society.